Community Empowerment through Capacity Strengthening for the Development of Bojongkulur Tourism Village - Christhe N, Theodosia; Kristiana, Yustisia; Pramezwary, Amelda (Jurnal Pengabdian Masyarakat Akademisi, 2026)
The development of tourism villages is a crucial strategy for enhancing community welfare. Bojongkulur Village in Bogor Regency has been designated as a tourism village since 2022; however, it still faces challenges in human resource (HR) readiness to manage tourism professionally. This Community Service Program (PkM), funded by the Directorate of Research and Community Service, Directorate General of Research and Development, Ministry of Higher Education, Science, and Technology, aims to enhance human resource capacity in Bojongkulur Tourism Village through tourism HR development training. The implementation methods include socialization, training, and evaluation. A total of 26 participants, consisting of managers and community members engaged in tourism activities, actively participated in this program. Evaluation results indicated a highly positive response, including increased participant knowledge and the relevance of the material to field needs. The program has proven effective in strengthening the community’s understanding and active role in the development of Bojongkulur Tourism Village. It is expected to contribute to improving governance and enhancing the competitiveness of Bojongkulur Tourism Village sustainably. Thus, this activity demonstrates a tangible impact in promoting community participation as the primary driver of community-based tourism development.